Struktur und Geste : "Informelle Malerei" und "subjektive Fotografie" in der deutschen Kunst der 50er Jahre. - Grimme, Ernst Günther; Oellers, Adam C.; Sachsse, Rolf (Aachen : Suermondt-Ludwig-Museum Aachen, 1988)
Berke, Hubert ; Brill, Fritz ; Brüning, Peter ; Buchheister, Carl ; Chargesheimer ; Claasen, Hermann ; Dahmen, Karl Fred ; Fathwinter ; Gaul, Winfred ; Götz, K.O. (Karl Otto) ; Hager, Anneliese ; Hahn, Helmut ; Hajek-Halke, Herbert ; Hoehme, Gerhard ; Hoepffner, Marta ; Jürgen-Fischer, Klaus ; Keetman, Peter ; Köhler, Reinhold ; Kreisel, Oskar ; Merfels, Helga ; Platschek, Hans ; Schultze, Bernard ; Schumacher, Emil ; Sonderborg, K.R.H. ; Steinert, Otto ; Thieler, Fred ; Trier, Hann ; Werden, Hubert ; Winter, Fritz
biografie, bibliografie
Struktur und Geste : "Informelle Malerei" und "subjektive Fotografie" in der deutschen Kunst der 50er Jahre, Suermondt-Ludwig-Museum, Aachen, 31.1. - 13.3.1988
Duits
boek
Keywords: Duitsland